Effect of nano SiC particles on properties and characterization of Magnesium matrix nano composites. (2019) - Vijayabhaskar, S.; Rajmohan, T.; Vignesh, T.K.; Venkatakrishnan, H.
Abstract: The increasing demand and diverse design requirements with significant weight savings as well as high strength-to-weight ratio as compared to conventional materials have all raised a growing interest towards the field of composites. Ceramic silicon carbide has received wide attention because of its excellent oxidation resistance, corrosion resistance and low density and even at high temperatures. In recent years, Magnesium (Mg) matrix composites have been used in the automotive industry owing to their lightweight property. Mg matrix composites compromise a very high specific strength, excellent castability, good damping capacity and greater machinability. Nanoparticle reinforcements can considerably improve the mechanical properties of the matrix by more successfully stimulating the particle hardening mechanisms than micron-sized particles. The present paper deals with the fabrication and characterization of magnesium matrix reinforced with different wt % (0, 0.5 and 1) of nano SiC particles prepared by solidification combined with ultrasonic cavitation process. Mechanical properties such as micro hardness and density and microstructure of the composites were observed. Microstructure of nano SiC composites were investigated by scanning electron microscope (SEM), X-ray diffraction (XRD) and Energy Dispersive X-ray (EDX). The results showed that the increase in weight % of nano SiC improve the mechanical properties.